A Qualitative and Quantitative Evaluation of Terpenoid and Alkaloid in Root and Stem of Pasak Bumi (Eurycoma longifolia Jack) - Anisa Rahmalia; Rizkita R. Esyanti; Iriawati Iriawati (Jurnal Matematika & Sains, 2011)
Herbal, as health solution, regained its popularity because many studies showed advantages of using it. One of the most industrially needed herbal materials is the extract of pasak bumi (Eurycoma longifolia Jack), which is popular for its alleged sexual-enhancing properties. E. longifolia was known to produce secondary metabolites, especially terpenoid and alkaloid. The presence of major alkaloids and terpenoids in root and stem of E. longifolia was evaluated quantitatively by analyzing the ethanol extract of root and stem of E. longifolia using GC-MS. Qualitative analysis was conducted through colorimetric test on both extracts by using Dragendorff and Lieberman-Burchad reagents. Colorimetric test showed that there was a difference in both terpenoid and alkaloid amounts on ethanol extract of both root and stem. GC-MS analysis showed that the ethanol extract of E. longifolia from the root contained 14.631% terpenoid and that from the stem was only 7.781%. The ethanol extract of E. longifolia from the stem contained 1.785 % of alkaloid, while that from the root was 5.117 % from total compounds. Major alkaloids found on both organs were 3-Methyl-1-oxo-2,3-dihydro-1H-pyrazolo[4,3-c][1,10] phenanthroline, which showed higher concentration in root. Major terpenoid in root included 2H-1-Benzopyran-2-one, 3-phenyl- (coumarin derivate), whilst that in stem was Stigmasterol. These substances have different activities in target cells. Therefore, the knowledge of active compounds in organ parts of pasak bumi will lead to a more efficient production process.